„nema take u jamerike ni u szvoj madzarske szamo j ima u dusnoku taku ko ti”: Neke jezične osobitosti dušnočkoga rackog govora u pismima iseljenika - Tamaskó, Eszter (SlavVaria, 2026)
“Nema take u Jamerike ni u szvoj Madzarske, szamo j ima u Dusnoku taku ko ti” – Some Linguistic Features of the Dusnok Rac Dialect in Emigrant Letters. The paper examines rare written records of the Dusnok Rac dialect, preserved in emigrant letters from the 20th century. It examines five letters by two senders, written in the United States in the Dusnok Rac dialect but recorded with Hungarian orthography. In addition to presenting the authors, the context of their writing, and the content of the correspondence, the corpus highlights phonological, morphological, and lexical features of the Slavonian dialect, along with instances of Hungarian and occasional English influence on Dusnok Rac speech. This small corpus offers a unique insight into the linguistic features of the Dusnok Rac community, and indirectly into its cultural and identity heritage.